The Political Market and the Party Financing in Bulgaria (UNWE Yearbook, 2014)
The study is realized some essential issues of the political market and party financing in Bulgaria during the transition period. Some theoretical foundations of this market, its genesis and development are discusses, as the main attention is paid to the nature and structure of the political market. It is highlightened the new role of the „political money“ for development of the „market of political ideas“ and their significance for the financing of the political parties in the 20th century.A special place is given to the material of the Bulgarian party financing parties of the Liberation until now. Here the emphasis is on the evolution of the legal regulation of the party financing in the country during 1990 – 2010. To thorough analysis are subjected and the key forms (and models) of the unregulated finance of the political parties during the transition („trade votes“, „buying“ voters, „the market of the political corruption“) that acquire alarming proportions in our political life.In the final part of the study are set out the main ways to reform the law on party financing, which are based on two major approaches: one by an independent single structural change in the current laws on party funding and the other through a complex reform of the political system in the country (including and of the specific legislation on party funding).